Polyester Film

A polyester film with optimized mechanical properties addresses the limitations of conventional films by enhancing deep drawability and electrolyte resistance, ensuring high-capacity battery exteriors and improved manufacturing efficiency.

JP7615593B2Active Publication Date: 2025-01-17TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020164818
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-01-17
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

Conventional polyester films used for battery exterior packaging exhibit insufficient deep drawability and electrolyte resistance, leading to issues such as film deterioration and reduced productivity during the battery manufacturing process.

Method used

A polyester film with specific properties, including a work hardening index of 1.6 to 3.0 in both longitudinal and width directions, intrinsic viscosity of 0.66 to 0.95, rigid amorphous content of 28% to 60%, and crystallinity of 25% to 40%, enhances deep drawability and electrolyte resistance by optimizing molecular structure and mechanical properties.

Benefits of technology

The film provides excellent electrolyte resistance and deep drawability, enabling the formation of battery exteriors with high capacity and various shapes without process defects, improving productivity and maintaining film integrity during heat sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615593000004
    Figure 0007615593000004
  • Figure 0007615593000005
    Figure 0007615593000005
  • Figure 0007615593000001
    Figure 0007615593000001
Patent Text Reader

Abstract

To provide a polyester film making it possible to obtain deep drawing properties similar to that obtained using polyamide in a construction in which a metal foil and a sealant layer are laminated one upon another, as a battery exterior or medicine packaging.SOLUTION: Work-hardening exponents in a longitudinal direction and a width direction of a polyester film are 1.6-3.0, and a difference between the work-hardening exponent in the longitudinal direction and that in the width direction is 0.5 or less. Inherent viscosity of the polyester film is 0.66-0.95, and a rigid amorphous content thereof is 28-60%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film that can be suitably used for battery exterior packaging and pharmaceutical packaging. [Background technology]

[0002] Lithium batteries, also called lithium secondary batteries, have liquid, gel-like polymers, solid polymers, or polymer electrolytes, and generate current by the movement of lithium ions. They include those in which the positive and negative electrode active materials are made of polymers. The lithium secondary battery is composed of a positive electrode current collector (aluminum, nickel), a positive electrode active material layer (polymer positive electrode materials such as metal oxides, carbon black, metal sulfides, electrolyte, polyacrylonitrile, etc.), an electrolyte layer (carbonate-based electrolytes such as propylene carbonate, ethylene carbonate, dimethyl carbonate, ethylene methyl carbonate, etc., inorganic solid electrolytes made of lithium salts, gel electrolyte), a negative electrode active material layer (polymer negative electrode materials such as lithium metal, alloys, carbon, electrolyte, polyacrylonitrile, etc.), a negative electrode current collector (copper, nickel, stainless steel), and an exterior body that packs them. In recent years, lithium batteries have been used in a wide range of fields due to their high volumetric and weight efficiency, and are used as small, high-capacity power sources in personal computers, mobile terminal devices (smartphones, etc.), video cameras, electric vehicles, energy storage batteries, robots, satellites, etc.

[0003] A typical exterior body for a lithium battery is a metal can made by pressing metal into a cylindrical or rectangular parallelepiped container. However, when a metal can is used, the shape of the battery itself is determined because the outer wall of the container is rigid, and the hardware side needs to be designed to match the battery, and the dimensions of the hardware using the battery are determined by the battery, resulting in a problem of design restrictions. Therefore, an exterior body in which two molded bodies formed by drawing and molding a component composed of a resin layer / aluminum / sealant layer into a square shape and laminating them with heat sealing has become popular. In the component, the sealant layer is responsible for heat sealing properties, the aluminum is responsible for barrier properties, and the resin layer is responsible for deep drawing properties. Recently, in the battery manufacturing process, a decrease in yield due to deterioration of the resin layer constituting the component due to leakage of electrolyte, etc. has been considered a problem, and in addition to being given deep drawing properties, the resin layer is required to have electrolyte resistance.

[0004] Up until now, for example, polyamide film has been used as the resin layer (see Patent Document 1, for example). However, polyamide film is not sufficiently moisture-proof and stable against electrolyte, and may deteriorate when electrolyte is attached during the battery manufacturing process, so improvements have been required. Also, in order to prevent deterioration of the polyamide film when electrolyte is attached during the battery manufacturing process, a configuration has been proposed in which polyester is provided on the outermost exterior (see Patent Documents 2 and 3), and although the formability is sufficient, there is a problem that productivity is poor because an extra process is required to bond the polyester film and polyamide.

[0005] Additionally, polyester films alone have also been investigated (see, for example, Patent Documents 4 and 5). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-236938 A [Patent Document 2] JP 2000-334891 A [Patent Document 3] Patent No. 6476679 [Patent Document 4] JP 2011-204674 A [Patent Document 5] Patent No. 6177475 Summary of the Invention [Problem to be solved by the invention]

[0007] However, although the deep drawability and electrolyte resistance are improved by using the polyester film, the deep drawability is insufficient compared to a configuration using a polyester film and a polyamide film. The present invention aims to provide a polyester film having improved deep drawability compared to a conventional polyester film alone. [Means for solving the problem]

[0008] In order to solve the above problems, the polyester film of the present invention has the following configuration. (1) The work-hardening index in both the longitudinal and transverse directions is 1.6 to 3.0, and the difference between the work-hardening indexes in the longitudinal and transverse directions is 0.5 or less, the intrinsic viscosity is 0.66 to 0.95, and the rigid amorphous amount is 28% to 60%. (2) The melting point is 248°C or higher. (3) The crystallinity is 25% or more and 40% or less. (4) The breaking elongation in both the longitudinal and transverse directions is 100% or more. (5) Used for battery exteriors. (6) Used for pharmaceutical packaging. Effect of the Invention

[0009] The polyester film of the present invention has excellent electrolyte resistance due to the use of a polyester resin, and by setting the work hardening index, intrinsic viscosity, and rigid amorphous amount within specific ranges, it is possible to achieve deep draw formability comparable to that of structures using polyamide, despite being polyester, and the film can be suitably used for battery exterior components compatible with high capacity and packaging components compatible with various shapes. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a schematic side view of a base consisting of a rectangular male mold and a rectangular female mold. [Diagram 2] FIG. 2 is a top view of a molded component in an evaluation of molding followability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The polyester film of the present invention has a work hardening index in both the longitudinal direction and the transverse direction of 1.6 to 3.0. The work hardening index is a value calculated from the stress at 5% elongation and the stress at 60% elongation obtained from a tensile test defined in the evaluation method (11) Work Hardening Index described later. The laminate material used for the battery exterior is typically configured by laminating an outermost film, a metal foil, and a sealant layer in this order, and in many cases, the outermost film is a single layer or composite structure, and is about 25 μm thick, the metal foil is 40 μm thick, and the sealant layer is about 80 μm thick, with the outermost film being the thinnest. The inventors have made extensive studies and have clarified that when drawing is performed with this structure, the neutral axis of the stress applied in the thickness direction is determined according to the work hardening state of each layer, and the position in the thickness direction at which the stress is concentrated is determined. When the work-hardening state of the outermost film, i.e., the work-hardening index, is less than 1.6, the neutral axis is biased toward the metal foil and sealant layer, and the metal foil is easily subjected to uneven stress, which results in breakage or pinholes in the metal foil during drawing. For this reason, the polyester film of the present invention must have a work-hardening index of at least 1.6. In order to prevent the neutral axis from being biased toward the outermost film, the work-hardening index must be 3.0 or less in both the longitudinal and transverse directions. It is preferably 2.0 or more and 2.6 or less.

[0012] In order to make the work hardening index of the polyester film in both the longitudinal and transverse directions 1.6 to 3.0, it is preferable to make the breaking strength in the longitudinal and transverse directions of the film 200 MPa or more. The longitudinal and transverse directions of the film are defined as any one direction (0°) of the film, and the breaking strength in the directions of 15°, 30°, 45°, 60°, 75°, 90°, 105°, 120°, 135°, 150°, and 165° from the direction, and the direction with the highest breaking strength is defined as the transverse direction, and the direction perpendicular to the transverse direction is defined as the longitudinal direction. In order to make the breaking strength of the polyester film 200 MPa or more, it is preferable to stretch it at a high ratio. Specifically, it is most preferable to stretch it biaxially, and it is preferable to stretch it by a known method at an areal stretching ratio of 11.0 times or more successively or simultaneously. If the work hardening index is less than 1.6, the drawing formability is poor. In addition, the higher the work hardening index, the greater the elastic deformation caused by bending during drawing, which tends to result in greater warpage after forming. For this reason, it is important to keep the work hardening index to a minimum according to the required degree of warpage.

[0013] In the present invention, from the viewpoint of in-plane uniformity, the difference in work hardening index between the longitudinal direction and the width direction is 0.5 or less. If the difference in work hardening index between the longitudinal direction and the width direction exceeds 0.5, the in-plane uniformity is low, and a load is applied non-uniformly during drawing, causing local deformation and resulting in poor drawability. The difference in work hardening index is preferably 0.3 or less.

[0014] In the present invention, it is preferable that the breaking elongation in both the longitudinal direction and the width direction is 100% or more. One of the deformation behaviors of materials in drawing is elongation. The greater the elongation of the film, the greater the element of deformation behavior that can be elongated, and the better the drawing processability. For this reason, it is preferable that the breaking elongation in both the longitudinal direction and the width direction is 100% or more. In order to make the breaking elongation in the longitudinal direction and the width direction 100% or more, it is possible to adjust the stretching ratio in both directions to 4.0 times or less. If there is a direction in which the stretching ratio exceeds 4.0 times, it is advantageous in increasing the work hardening index, but the breaking elongation in the stretching direction becomes 100% or less, and the drawing formability may decrease.

[0015] The polyester film of the present invention has a rigid amorphous amount of 28% or more and 60% or less relative to the entire film. Here, the rigid amorphous amount is a value measured by the method described in (9) Rigid Amorphous Amount described later. When the rigid amorphous amount is within this range, it is possible to obtain a particularly remarkable piercing resistance, which is a characteristic in the thickness direction. The drawing process that is often performed in battery exterior laminate materials is a process in which the four corners are fixed with a mold and the film is drawn in the thickness direction. By controlling the rigid amorphous amount relative to the entire film within this range, excellent drawing characteristics are exhibited in the above-mentioned drawing process. When the rigid amorphous amount exceeds 60%, the amorphous component occupies the majority of the film bulk composition, and the dimensional stability of the film is significantly reduced. On the other hand, when the rigid amorphous amount is less than 28%, the piercing resistance, which is a characteristic in the thickness direction, is poor. The film bulk state is determined by the crystallinity of the raw material used as well as the film-forming conditions. For example, when polyethylene terephthalate is used, in order to make the rigid amorphous amount 28% or more, it is important to make the plane orientation coefficient fn of the film at least 0.165 or more. Here, the plane orientation coefficient of the film is measured by the method described in Evaluation Method (5) Planar Orientation Coefficient fn of Polyester Film, which will be described later. In order to make the plane orientation coefficient of the film 0.165 or more, a method of making the areal stretching ratio during biaxial stretching 12.25 times or more can be mentioned. In addition, it is preferable to control the rigid amorphous by the heat treatment temperature after the successive biaxial stretching, and it is important to make the highest temperature (heat treatment temperature) applied during film formation 200 ° C or less. On the other hand, even if the heat treatment temperature is set to 230 ° C or more, the rigid amorphous amount tends to increase due to the initiation of melting of the resin, but since this promotes crystallization of the film by heat, the crystallization degree described later increases, and the crystallization degree becomes higher than the rigid amorphous as a film bulk configuration. For this reason, it is important to make the heat treatment temperature 200 ° C or less. If the heat treatment temperature of the film is more than 200 ° C and less than 230 ° C, the rigid amorphous amount may be less than 28%.

[0016] The polyester film of the present invention preferably has a crystallinity of 25% or more and 40% or less. The crystallinity can increase the mechanical strength of the film by orientation crystallization due to stretching or heat crystallization. If the crystallinity is less than 25%, the film plane orientation may be insufficient and the work hardening index may not be controlled within the range of the present invention, and if the crystallinity is more than 35%, the rigid amorphous amount may not be controlled within the range of the present invention. In order to adjust the crystallinity to 25% or more and 40% or less, for example, a homopolyester resin is used, the plane orientation coefficient of the film is set to 0.165 or more and 0.170 or less, and the heat treatment temperature is set to 150°C or more and 200°C or less, but other resins may be mixed.

[0017] The polyester film of the present invention has an intrinsic viscosity of 0.66 or more and 0.95 or less. Here, the intrinsic viscosity is a value measured by the method described in (4) Intrinsic Viscosity described later. When the intrinsic viscosity is within this range, the entanglement of molecular chains increases, and deformation in the thickness direction, particularly puncture resistance, can be obtained. When the intrinsic viscosity is less than 0.66, the entanglement of molecular chains is insufficient, and sufficient drawing processability cannot be obtained. On the other hand, when the intrinsic viscosity exceeds 0.95, the filtration pressure during melt film formation increases, so the discharge amount has to be reduced, resulting in poor productivity. The intrinsic viscosity can be adjusted by the raw material used for melt film formation, and if the intrinsic viscosity of the film is to be increased, it is preferable to increase the intrinsic viscosity of the raw material used during film formation. Considering both the molecular chain entanglement effect and productivity, the intrinsic viscosity is preferably 0.69 or more and 0.88 or less.

[0018] The polyester film of the present invention preferably has a 150°C heat shrinkage rate of 3.5% or more and 14.0% or less in both the longitudinal and transverse directions. In the lamination process in which heat of about 150°C is applied, such as the extrusion lamination process in which molten resin is directly laminated on the film, using the polyester film of the present invention, in order to suppress wrinkles during extrusion lamination, the 150°C heat shrinkage rate is preferably 3.5% or more. On the other hand, if the heat shrinkage rate of the temperature applied during lamination exceeds 14%, the film may be deformed too much during lamination due to heat shrinkage during lamination, causing problems. From the viewpoint of achieving both wrinkles and thermal deformation during lamination, the polyester film of the present invention preferably has a 150°C heat shrinkage rate of 10% or less in the longitudinal and transverse directions. In order to control the 150°C heat shrinkage rate in the longitudinal and transverse directions to 3.5% or more and 14.0% or less, it is possible to control the film area magnification to 12.25 times or more and to heat treat the film at a heat treatment temperature of 160°C or more and 200°C or less.

[0019] The polyester film of the present invention preferably has a melting point (melting endothermic peak temperature (Tm)) of 248°C or higher as determined by a differential scanning calorimeter. When the polyester film of the present invention is used as a battery exterior material, the sealant layers are heat-sealed together to form a container. For this reason, it is necessary to suppress melting of the exterior film by the heat of heat sealing. If the melting endothermic peak temperature Tm is less than 248°C, it is necessary to lower the heating temperature when performing heat sealing, and as a result of the increased time required for forming a container by heat sealing, mass productivity may be poor. In order to make the melting endothermic peak temperature Tm 248°C or higher, it is most preferable to use a homopolyester. From the viewpoint of processability, it is preferable that it is 320°C or lower.

[0020] The polyester film of the present invention is mainly composed of polyester. Polyester is a general term for polymer compounds in which the main bond in the main chain is an ester bond. Polyester can usually be obtained by polycondensation reaction of dicarboxylic acid or its derivative with diol or its derivative, and electrolyte resistance can be obtained by using polyester as the main component. In the present invention, "mainly composed" refers to a ratio of 60% by mass to 100% by mass of the entire object, and here refers to the ratio of the polyester film. Here, the dicarboxylic acid unit (structural unit) or diol unit (structural unit) means a divalent organic group excluding the portion removed by polycondensation, and is represented by the following general formula.

[0021] Dicarboxylic acid unit (structural unit): -CO-R-CO- Diol unit (structural unit): -O-R'―O- (Here, R and R' are divalent organic groups. R and R' may be the same or different.) Examples of diols or derivatives thereof which give the polyester used in the present invention include, in addition to ethylene glycol, aliphatic dihydroxy compounds such as 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and neopentyl glycol; polyoxyalkylene glycols such as diethylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; alicyclic dihydroxy compounds such as 1,4-cyclohexanedimethanol and spiroglycol; aromatic dihydroxy compounds such as bisphenol A and bisphenol S, and derivatives thereof. Examples of dicarboxylic acids or derivatives thereof that provide the polyester used in the present invention include, in addition to terephthalic acid, aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenoxyethanedicarboxylic acid, and 5-sodiumsulfonedicarboxylic acid, aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, sebacic acid, dimer acid, maleic acid, and fumaric acid, alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, and oxycarboxylic acids such as paraoxybenzoic acid, as well as derivatives thereof. Examples of dicarboxylic acid derivatives include esters of dimethyl terephthalate, diethyl terephthalate, 2-hydroxyethyl methyl terephthalate, dimethyl 2,6-naphthalenedicarboxylate, dimethyl isophthalate, dimethyl adipate, diethyl maleate, and dimethyl dimerate.

[0022] The polyester film of the present invention may have a single layer structure or a multi-layer structure of two or more layers. In the case of a multi-layer structure, a symmetrical structure with respect to a central layer such as B layer / A layer / B layer is preferable from the viewpoint of suppressing warpage after film formation. If warpage occurs after film formation, the handling property may be deteriorated in the subsequent battery manufacturing process. In addition, in the present invention, a five-layer structure such as B / A / B / A / B may be used. In the case of a multi-layer structure, a three-layer laminate structure of B / A / B is preferable from the viewpoint of warpage after film formation. In the present invention, if the film has a two-layer structure such as A layer / B layer with different molecular orientations, warpage may occur immediately after film formation. However, an asymmetric structure such as a two-layer structure of A / B may be used as long as it does not impair the effects of the present invention. In order to improve the drawing property, the polyester film of the present invention preferably has a dynamic friction coefficient μd of 0.3 or less on the contact surface on the die side. By setting the dynamic friction coefficient in the above range, the deformation resistance during drawing is reduced, and the processability is improved. There is no particular limitation on how to set the dynamic friction coefficient to 0.3 or less, but for example, it is preferable that the outermost layer has a layer containing 0.3 mass % or more and 5 mass % or less of inorganic particles and / or organic particles with an average particle size of 0.005 μm to 10 μm. More preferably, it is 0.5 mass % to 3 mass %. However, if the particles are added too much, the breaking elongation of the composite may decrease. For this reason, it is important to add particles within a range that does not impair the present invention. In the present invention, particles with an average primary particle size of 0.005 μm or more are used. The particle size referred to here means the number average particle size, and means the particle size observed in the cross section of the film. If the shape is not a perfect circle, the value converted to a perfect circle with the same area is taken as the particle size. Here, the number average particle size Dn can be obtained by the following steps (1) to (4). (1) First, a cross section of the film is cut in the thickness direction using a microtome without crushing it, and a magnified observation image is obtained using a scanning electron microscope. At this time, the cut is made in a direction parallel to the TD direction (transverse direction) of the film. (2) Next, for each particle observed in the cross section of the image, the cross-sectional area S is calculated, and the particle size d is calculated using the following formula.

[0023] d=2×(S / π) 1 / 2 (3) Using the obtained particle diameter d and the number of resin particles n, Dn is calculated according to the following formula.

[0024] Dn = Σd / n where Σd is the sum of the particle diameters in the observation area, and n is the total number of particles in the observation area. (4) The above steps (1) to (3) are carried out at five different locations, and the average value is the number-average particle size of the particles. 2 The above evaluation will be carried out in the above areas.

[0025] As the inorganic particles, for example, wet and dry silica, colloidal silica, aluminum silicate, titanium oxide, calcium carbonate, calcium phosphate, barium sulfate, aluminum oxide, mica, kaolin, clay, etc. can be used. As the organic particles, particles containing styrene, silicone, acrylic acids, methacrylic acids, polyesters, divinyl compounds, etc. as constituents can be used. Among them, it is preferable to use inorganic particles such as wet and dry silica, alumina, calcium carbonate, etc., and particles containing styrene, silicone, acrylic acid, methacrylic acid, polyester, divinylbenzene, etc. as constituents. Furthermore, these inorganic particles and organic particles may be used in combination of two or more kinds. It is also preferable to apply uneven processing such as embossing and sandblasting to the film surface in order to control the maximum surface height.

[0026] The thickness of the polyester film of the present invention is preferably 9 μm or more and 30 μm or less from the viewpoint of molding followability when made into a structure and warping after molding. Most preferably, it is 12 μm or more and 28 μm or less. Although it depends on the required drawing depth, if it is less than 9 μm, moldability may be poor, and if it is 30 μm or more, rigidity is high and warping may occur after molding.

[0027] In order to improve the adhesion to the adhesive layer, the polyester film used in the present invention may be subjected to a surface treatment such as corona treatment, plasma treatment, ozone treatment, or provision of an anchor coat layer. Examples of methods for forming an anchor coat layer include methods for coating a resin on the film surface (composite melt extrusion method, hot melt coating method, in-line coating method using a solvent other than water, water-soluble and / or water-dispersible resin, offline coating method, etc.). Among these, an in-line coating method in which a coating agent is applied to one side of a film before the orientation crystallization is completed, stretched in at least one direction, and heat-treated to complete the orientation crystallization is preferred in terms of uniform coating formation and productivity. In addition, when an anchor coat layer is provided, the resin is not particularly limited, but for example, acrylic resins, urethane resins, polyester resins, olefin resins, fluorine resins, vinyl resins, chlorine resins, styrene resins, various graft resins, epoxy resins, silicone resins, etc. can be used, and mixtures of these resins can also be used. From the viewpoint of adhesion, it is preferable to use polyester resins, acrylic resins, or urethane resins. When a polyester resin is used as a water-based coating liquid, a water-soluble or water-dispersible polyester resin is used, and in order to make it water-soluble or water-dispersible, it is preferable to copolymerize a compound containing a sulfonate group or a compound containing a carboxylate group. When an acrylic resin is used as a water-based coating liquid, it is necessary to make it dissolved or dispersed in water, and a surfactant (such as, but not limited to, a polyether compound) may be used as an emulsifier. In addition, in the anchor coat layer used in the present invention, various crosslinking agents can be used in combination with the resin to further improve adhesion. As the crosslinking agent resin, a melamine-based, epoxy-based, or oxazoline-based resin is generally used. The polyester film of the present invention can be used in combination with various materials. For example, as the metal foil, aluminum, stainless steel, copper, nickel, titanium, tin, silver, gold, zinc, iron, etc. can be used depending on the purpose. Among them, a layer containing aluminum is preferable from the viewpoints of formability, gas barrier property, water vapor barrier property, strength, and economical efficiency. The metal foil may be aluminum alone, or may be an aluminum alloy to which copper, zinc, manganese, magnesium, silicon, lithium, iron, etc. are added. The aluminum content of the metal foil is preferably 95 mass% or more, and pure aluminum or aluminum / iron alloys are preferably used.

[0028] The method of compounding the polyester film of the present invention with various materials is not particularly limited, but from the viewpoint of adhesion, dry lamination is preferably used, in which an adhesive layer made of an adhesive is provided and bonded. The adhesive used may be a thermosetting type or a thermoplastic type, but a thermosetting type is preferable. For example, adhesives made of polyurethane resin, polyester resin, polyvinyl chloride resin, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, methyl methacrylate-butadiene copolymer, chloroprene, rubber resin such as polybutadiene, polyacrylic acid ester resin, polyvinylidene chloride resin, polybutadiene, or carboxyl modified products of these resins, epoxy resin, cellulose derivative, ethylene vinyl acetate copolymer, polyethylene oxide, acrylic resin, lignin derivative, etc. are mentioned. From the viewpoint of adhesion between the surface treatment surface of the polyester film and the metal foil, adhesives made of polyurethane resin and polyester resin are preferable.

[0029] In the present invention, the composite can be used as a structure in which a sealant layer is further provided on the composite from the viewpoint of improving heat sealability and barrier property, and the structure is arranged in the order of polyester film / adhesive layer / metal foil / sealant layer. By using the above structure for battery exterior, a battery packaging material excellent in electrolyte resistance and squeeze formability can be obtained. Examples of the sealant layer include ethylene-based resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, and ethylene-butene copolymers, propylene-based resins such as homopolypropylene, ethylene-propylene copolymer, and ethylene-propylene-butene copolymers, methylpentene resins, and cyclic olefin resins, polyvinyl chloride, copolymers of ethylene, propylene, vinyl acetate, allyl chloride, allyl glycidyl ether, acrylic acid esters, methacrylic acid esters, vinyl ethers, etc., which can be copolymerized with vinyl chloride monomers, and mixtures thereof.

[0030] The polyester film of the present invention is preferably used for battery exteriors. In order to maintain battery performance, the battery exteriors require water vapor barrier properties to prevent the intrusion of water vapor, electrolyte resistance to prevent swelling with electrolyte and deterioration of the outermost exterior due to electrolyte leakage during the manufacturing process, and deep drawability to meet the needs for high capacity. By using the polyester film of the present invention, it has excellent deep drawability comparable to that of a polyamide-based structure, and by applying it to battery exterior applications, it is possible to achieve excellent productivity without process problems and to meet the needs for high capacity.

[0031] The polyester film of the present invention is also preferably used for pharmaceutical packaging. Pharmaceutical packaging requires gas barrier properties and water vapor barrier properties to prevent deterioration of the contents, and is required to be printable so as to meet the specifications for printing. Furthermore, there is an increasing need for deep draw formability that can accommodate contents of various shapes. In order to achieve high gas barrier properties and water vapor barrier properties, it is preferable to have a metal foil, but since deep draw forming is difficult for metal foils, it is necessary to laminate a film and mold it following the film. By using the polyester film of the present invention, the deep draw formability of a composite laminated with various materials is good, and by applying it to pharmaceutical packaging applications, it can be applied to medicines corresponding to various shapes.

[0032] The outline of the polyester film manufacturing method of the present invention will be illustrated. First, a polyester film is formed. For this purpose, the above-mentioned polyester raw material is melt-extruded by a known method, and the polyester is adhered to a casting drum adjusted to about 10°C to 35°C so as not to crystallize, to obtain a cast sheet. The adhesion method may be a known method such as an electrostatic application method or an air knife method. Next, the obtained cast sheet is biaxially stretched and oriented by a known method. The biaxial stretching may be a known method such as a sequential biaxial, simultaneous biaxial, or tubular method. During stretching, an anchor coat layer may be coated after uniaxial stretching in some cases. Here, it is important to set the stretch area ratio, which is the product of the stretch ratios of the first axis and the second axis, to 12.25 times or more in order to make the average work hardening index in the longitudinal direction and the width direction of the polyester film 1.6 or more. For the same reason, the stretching temperature is preferably set to be equal to or higher than the glass transition temperature of the resin and equal to or lower than the glass transition temperature + 15°C. However, this is not limited as long as the effect of the present invention can be obtained. After biaxial stretching, it is preferable to perform heat treatment from the viewpoint of dimensional stability and the like. The heat treatment temperature is important in controlling the rigid amorphous amount, and it is important to set it to 200°C or less. From the viewpoint of dimensional stability, the heat treatment temperature is preferably 150°C or more. In this case, the heat treatment time is preferably in the range of 1 second to 120 seconds or less. After the heat treatment, a surface treatment such as corona treatment is performed as necessary to improve adhesion to various materials, etc., to obtain a polyester film. EXAMPLES

[0033] In the following, Examples 7, 8, and 12 shall be read as Reference Examples 7, 8, and 12. (Evaluation method) Polyester films, composites and structures were produced and evaluated by the following methods.

[0034] (1) Polyester composition The polyester resin and film were dissolved in hexafluoroisopropanol (HFIP), 1 H-NMR and 13The contents of each monomer residue and the by-product diethylene glycol were quantified using C-NMR.

[0035] (2) Film thickness, layer thickness When measuring the thickness of the entire film, the film was cut into 200 mm × 300 mm pieces using a dial gauge, and the thickness was measured at five arbitrary locations on each sample, and the average was calculated. The thickness of each layer of the film, composite, and construct was determined by embedding the sample in epoxy resin, cutting out the film cross section with a microtome, and observing the cross section with a transmission electron microscope (TEM H7100, manufactured by Hitachi, Ltd.) at a magnification of 5000 times.

[0036] (3) Longitudinal and transverse directions of polyester film In the present invention, the breaking strength was measured in any one direction (0°) of the film and in directions at 15°, 30°, 45°, 60°, 75°, 90°, 105°, 120°, 135°, 150°, and 165° from the direction, and the direction with the highest breaking strength was defined as the width direction, and the direction perpendicular to the width direction was defined as the longitudinal direction. The breaking strength can be obtained by the method described in (8) Breaking strength of polyester film.

[0037] (4) Intrinsic viscosity The solution viscosity of the polyester film of the present invention was measured in orthochlorophenol at 25°C using an Ostwald viscometer, and the intrinsic viscosity was calculated from the solution viscosity. The unit of intrinsic viscosity is [dl / g]. The number of n was 3, and the average value was used.

[0038] (5) Planar orientation coefficient fn of polyester film Using an Abbe refractometer, the layer to be measured for the plane orientation coefficient (hereinafter referred to as the measurement layer) was adhered to the glass surface, and the refractive indices (Nx, Ny, Nz) in the a direction, b direction, and thickness direction were measured using sodium D line as a light source, and the plane orientation coefficient fn of the measurement layer was calculated using the following formula. Plane orientation coefficient fn=(Nx+Ny) / 2-Nz (6) Breaking elongation The film and the composite were cut into a rectangular sample of 150 mm long x 10 mm wide in the longitudinal and transverse directions. Under the conditions of 25°C and 63% Rh, a tensile test was performed in the longitudinal and transverse directions of the film using a tensile tester (Orientec Co., Ltd., automatic film strength and elongation measuring device "Tensilon AMF / RTA-100") at a crosshead speed of 300 mm / min, a width of 10 mm, and a sample length of 50 mm. The value of the elongation at break was taken as the breaking elongation. The measurement was performed five times, and the average was used.

[0039] (7) Crystallinity According to JIS K7122 (1999), a differential scanning calorimeter robot DSC-RDC220 manufactured by Seiko Denshi Kogyo Co., Ltd. and a "Disk Session" SSC / 5200 were used for data analysis, and 5 mg of the film sample was heated from room temperature to 300°C at a heating rate of 20°C / min on an aluminum tray and held at 300°C for 5 minutes. The endothermic peak heat ΔHm, cold crystallization heat ΔHc, and melting heat ΔHm0 (140.1 J / g) of perfectly crystalline PET were used to calculate the heat of melting ΔHm0 (140.1 J / g) of perfectly crystalline PET according to the following formula. Crystallinity (%)=(ΔHm-ΔHc) / ΔHm0x100 (8) Rigid amorphous amount The rigid amorphous amount was calculated from the mobile amorphous amount and the degree of crystallinity obtained by the measurement according to the following calculation formula. Rigid amorphous amount (%) = 100-(movable amorphous amount + crystallinity). The theoretical specific heat difference of completely amorphous polyethylene terephthalate = 0.4052 J / (g℃) In the present invention, the theoretical value of the specific heat difference of a completely amorphous material of polyethylene terephthalate was referred to.

[0040] The mobile amorphous amount was measured as follows. Using a TA Instruments temperature modulated DSC, 5 mg of sample was measured in a nitrogen atmosphere from 0°C to 150°C at a heating rate of 2°C / min, with a temperature modulation amplitude of ±1°C and a temperature modulation period of 60 seconds. The specific heat difference at the glass transition temperature obtained by the measurement was determined and calculated using the following formula. Mobile amorphous amount (%) = (specific heat difference) / (theoretical specific heat difference of completely amorphous polyester) x 100 The theoretical specific heat difference of completely amorphous polyethylene terephthalate = 0.4052 J / (g℃) In the present invention, for those containing 70 mol % or more of polyethylene terephthalate units, the theoretical value of the specific heat difference of a completely amorphous material of polyethylene terephthalate was referenced.

[0041] (9) Glass transition temperature Tg, melting point (melting endothermic peak temperature Tm) In accordance with JIS7122 (1999), using a differential scanning calorimeter (EXSTAR DSC6220 manufactured by Seiko Instruments), 3 mg of resin was heated in a nitrogen atmosphere from 30°C to 300°C at a rate of 20°C / min. Then, after holding at 300°C for 5 minutes, the temperature was lowered to 30°C at a rate of 40°C / min. After further holding at 30°C for 5 minutes, the temperature was raised from 30°C to 300°C at a rate of 20°C / min. The glass transition temperature obtained during this temperature rise was calculated by the following formula (i). Glass transition temperature = (extrapolated glass transition onset temperature + extrapolated glass transition finish temperature) / 2 (i) Here, the extrapolated glass transition onset temperature is the temperature at the intersection of a straight line extending the low-temperature baseline to the high-temperature side and a tangent drawn at the point where the gradient of the curve of the step-like change in the glass transition is maximum. The extrapolated glass transition end temperature is the temperature at the intersection of a straight line extending the high-temperature baseline to the low-temperature side and a tangent drawn at the point where the gradient of the curve of the step-like change in the glass transition is maximum. In addition, the peak top of the endothermic peak associated with the crystal melting of the resin is taken as the melting point (melting endothermic peak temperature Tm).

[0042] (10) Work hardening index The film was cut into a rectangular sample of 150 mm long x 10 mm wide in the longitudinal and transverse directions. Under the conditions of 25°C and 63% RH, a tensile test was performed in the longitudinal and transverse directions of the film at a crosshead speed of 300 mm / min, a width of 10 mm, and a sample length of 50 mm using a tensile tester (Orientec Co., Ltd., automatic film strength and elongation measuring device "Tensilon AMF / RTA-100"). 0(mm), length at 5% elongation is L 1 (mm), nominal stress at 5% elongation is P 1 (MPa), length at 60% elongation is L 2 (mm), where P is the nominal stress at 60% elongation 2 When the strain is expressed in MPa, the true strain at 5% elongation is calculated from equation (1), the true strain at 60% elongation from equation (2), the true stress at 5% elongation from equation (3), and the true stress at 60% elongation from equation (4). From the values ​​obtained from (1) to (4), the slope obtained from the equation when the X-axis is the true strain and the Y-axis is the true stress was taken as the work hardening index. This was measured five times in each of the longitudinal direction and the width direction, and the average value was used.

[0043] True strain at 5% elongation = Ln(L 1 / L 0 ) · · · (1) True strain at 60% elongation = Ln(L 2 / L 1 ) · · · (2) True stress at 5% elongation = P 1 (1+Ln(L 1 / L 0 ))···(3) True stress at 60% elongation = P 2 (1+Ln(L 2 / L 1 ))···(4) *Ln: natural logarithm (11) Heat shrinkage rate of polyester film at 150℃ in the transverse and longitudinal directions The film was cut into a rectangular sample measuring 150 mm long and 10 mm wide in both the longitudinal and transverse directions. Marked lines were drawn on the sample at 100 mm intervals, and the sample was heat-treated by hanging a 3 g weight and placing it in a hot air oven heated to 150°C for 30 minutes. The distance between the marks after heat treatment was measured, and the heat shrinkage rate was calculated from the change in the distance between the marks before and after heating, which was taken as the heat shrinkage rate. Measurements were performed on five samples in both the longitudinal and transverse directions, and the average value was used for evaluation.

[0044] (12) Dynamic friction coefficient of polyester film Using a slip tester manufactured by Toyo Seiki Co., Ltd., the stable region of resistance value after the initial rise when both sides of the film were rubbed together was measured according to JIS-K7125 (1999), and the dynamic friction coefficient μd was calculated. The sample was a rectangle with a width of 80 mm and a length of 200 mm, and three sets (6 pieces) were cut from the roll in the longitudinal direction of the rectangle. The measurement was performed three times, and the average value was calculated.

[0045] (13) Draw formability (a) How to create the construct The construct is obtained by bonding the polyester film or polyamide film of the present invention (here, Bonyl RX25μm manufactured by Kohjin Co., Ltd. was used) and the metal foil via an adhesive layer. The adhesive constituting the adhesive layer is a urethane adhesive "AD502" manufactured by Toyo Ink Co., Ltd. as the main agent and CAT10L manufactured by the same company as the crosslinking agent. AD502, CAT10L, and ethyl acetate are mixed in a mass ratio of 15:1.5:25 and applied to the metal foil at a thickness of 5g / m by dry lamination method. 2 The adhesive was applied uniformly to the surface-treated surface of the polyester film or polyamide film so that the adhesive was uniformly applied to the surface of the polyester film or polyamide film, and the non-chemically treated surface of the metal foil and the adhesive-coated surface of the polyester film or polyamide film were pressed against a roll heated to 80°C at 0.5 MPa and then rolled up. After that, an aging treatment was performed at 60°C for 7 days to obtain a composite.

[0046] (b) Method for preparing the complex A two-layer co-extruded film (maleic acid-modified polypropylene resin layer: 20 μm, polypropylene resin layer: 60 μm) of maleic acid-modified polypropylene resin and polypropylene as a sealant layer was placed on the metal foil of the structure prepared in (a) so that the maleic acid-modified polypropylene resin layer was adhered to the metal foil side that had been subjected to chemical conversion treatment, and a laminator was used to heat-press the composite described in the Examples and Comparative Examples and the metal foil side to produce a structure consisting of polyester film or polyamide film / adhesive layer / metal foil / sealant layer.

[0047] The construct obtained in (b) was cut into a size of 100 mm x 100 mm, and a mold consisting of a 50 mm x 30 mm rectangular male mold (R of the corner between the surface in contact with the construct and the side: 2 mm, Fig. 1) and a female mold with a clearance of 0.5 mm from the male mold (R of the corner between the surface in contact with the construct and the side: 2 mm, Fig. 1) was used to set the construct on the female mold so that the sealant side was on the male mold side, and press molding (pressure: 0.1 MPa, one shot 10 seconds) was performed, and evaluation was performed according to the following criteria. If pinholes or tears occurred in the laminate material after deep drawing, it was considered that deep drawing was not possible. S: Deep drawing was possible by more than 1 mm compared to polyamide structure. A: Deep drawing molding equivalent to that of polyamide structure was possible. B: The drawing depth was within 1 mm lower than the A rating. C: The drawing depth was within 1 mm lower than the B rating. D: The deep drawing molding was inferior to the C evaluation.

[0048] (14) Wrinkles during extrusion lamination (13) Draw formability (b) A 60,000 mm2 sample cut from a composite obtained by the method described in the composite production method 2 The appearance was visually inspected and judged as follows: A: No wrinkles were observed on the entire film. △: Wrinkles of 5 mm or more were observed.

[0049] (Manufacture of polyester film) The resin constituting the polyester film used for film formation was a mixture of main raw materials, auxiliary raw materials, and particle masters in the types and ratios shown in Table 1 for each Example and Comparative Example. The main raw materials, auxiliary raw materials, and particle masters used in each Example and Comparative Example were prepared as follows. Polyester A A polyethylene terephthalate resin (intrinsic viscosity 0.72) having 100 mol % terephthalic acid as the dicarboxylic acid component and 100 mol % ethylene glycol as the glycol component. Polyester B A polyethylene terephthalate resin (intrinsic viscosity 0.82) having 100 mol % terephthalic acid as the dicarboxylic acid component and 100 mol % ethylene glycol as the glycol component. Polyester C A polyethylene terephthalate resin (intrinsic viscosity 0.92) having 100 mol % terephthalic acid as the dicarboxylic acid component and 100 mol % ethylene glycol as the glycol component. Polyester D Polybutylene terephthalate resin (intrinsic viscosity 1.2) containing 100 mol % terephthalic acid as the dicarboxylic acid component and 100 mol % 1-4 butanediol as the glycol component. Polyester E A polyethylene terephthalate resin (intrinsic viscosity 0.65) having 100 mol % terephthalic acid as the dicarboxylic acid component and 100 mol % ethylene glycol as the glycol component. Particle Master A Polyethylene terephthalate particle master containing aggregated silica particles with an average particle size of 1.2 μm at a particle concentration of 2 mass% in polyester A. Particle Master B Polybutylene terephthalate particle master containing aggregated silica particles with an average particle size of 1.2 μm at a particle concentration of 2 mass % in polyester D.

[0050] (Coating Agent A) Examples 1 to 11, Comparative Examples 1 to 3 Acrylic resin consisting of a copolymer composition of methyl methacrylate / ethyl acrylate / acrylic acid / N-methylolacrylamide = 63 / 35 / 1 / 1 mass%: 3.00 mass% Melamine crosslinker: 0.75% by weight Colloidal silica particles (average particle size: 80 nm): 0.15% by mass Hexanol: 0.26% by mass Butyl cellosolve: 0.18% by mass ·Water: 95.66% by mass (Metal foil) The metal foil used in the present invention is as follows: Metal foil A "8021" is a 40μm thick aluminum foil made in Japan, with chromate treatment applied to both sides of the metal foil as a chemical conversion treatment.

[0051] (Examples 1 to 12, Comparative Examples 1 to 2) Using an extruder, the polyester species and particle master listed in Table 1 were each dried in a vacuum dryer at 180 ° C for 4 hours to thoroughly remove moisture, and then the main raw materials, auxiliary raw materials, and particle master were charged into the extruder as listed in Table 1 and melted at 280 ° C. The resin melt-extruded from the extruder and discharged from the die were cooled and solidified on a cast drum cooled to 25 ° C to obtain an unstretched sheet. At that time, the distance between the lip of the T-die and the cooling drum was set to 35 mm, and electrostatic voltage was applied at a voltage of 14 kV using a wire-shaped electrode with a diameter of 0.1 mm to adhere to the cooling drum. The speed at which the unstretched sheet passed through the cooling drum was 25 m / min, and the contact length of the unstretched sheet with the cooling drum was 2.5 m.

[0052] Next, the unstretched sheet was preheated with a group of rolls heated to the temperature shown in Table 2, and then stretched in the longitudinal direction (machine direction) to the ratios shown in Table 2 using heated rolls controlled to the temperature shown in Table 2, and cooled with a group of rolls at a temperature of 25°C to obtain a uniaxially stretched film.

[0053] This uniaxially stretched film was subjected to a corona discharge treatment in air, and the coating material A was mixed as an anchor coat layer on the treated surface while being ultrasonically dispersed, and was evenly applied to the surface bonded to the cast using a #4 metaling bar to perform a surface treatment. Next, while holding both ends of the uniaxially stretched film with clips, it was introduced into a preheating zone in a tenter controlled to a temperature listed in Table 2, and then continuously stretched in a heating zone maintained at a temperature listed in Table 2 in a direction perpendicular to the longitudinal direction (width direction) to a ratio listed in Table 2. Further, in a heat treatment zone in the tenter, heat treatment was performed for 20 seconds at a heat treatment temperature listed in Table 2, and further relaxation treatment was performed at a relaxation temperature listed in Table 2 with a relaxation ratio listed in Table 2. Next, it was uniformly cooled slowly to obtain a polyester film with a thickness listed in Table 1. The properties of the polyester film are as shown in Table 3.

[0054] The surface-treated side of the obtained polyester film was bonded to the metal foil A by dry lamination using a coating material made by mixing a urethane adhesive, Toyo Ink Co., Ltd.'s "AD502", CAT10L, and ethyl acetate in a ratio of 25:15:2, as an adhesive layer. The amount of adhesive applied was 5 g / m2 on the surface-treated side of the polyester film as solid content. 2 After lamination, the pieces were aged at 60°C for 144 hours to obtain a composite. The properties of the composite are shown in Table 3.

[0055] On the metal foil A of the obtained composite, a two-layer co-extrusion film (maleic acid-modified polypropylene resin layer: 20 μm, polypropylene resin layer: 60 μm) of maleic acid-modified polypropylene resin and polypropylene as a sealant was laminated by hot pressing (160 ° C, 0.3 MPa, 2 m / min) using a laminator so that the maleic acid-modified polypropylene resin layer was located on the metal foil side, and a polyester film / adhesive layer / aluminum foil / sealant structure was prepared. The evaluation results of the obtained structure are shown in Table 3, and it was confirmed that Examples 1 to 12 have excellent draw formability.

[0056] [Table 1]

[0057] [Table 2]

[0058] [Table 3] [Industrial Applicability]

[0059] The polyester film of the present invention exhibits draw formability equal to or better than that of a composition using polyamide by setting the work hardening index, intrinsic viscosity, and rigid amorphous amount within specific ranges, and can be suitably used for battery exterior components compatible with high capacity and pharmaceutical packaging components compatible with various shapes. [Explanation of symbols]

[0060] 1. Construct 2 Male mold 3 Female mold 4 Molded body

Claims

1. A polyester film having a work-hardening index in both the longitudinal and transverse directions of 1.6 to 3.0, a difference between the work-hardening indexes in the longitudinal and transverse directions of 0.5 or less, an intrinsic viscosity of 0.66 to 0.95, a rigid amorphous amount of 28% to 60%, and a heat shrinkage rate at 150°C in both the longitudinal and transverse directions of 3.5% to 10% (however, this does not include a polyester film in which an arbitrary direction on the film surface is taken as 0°, and the elastic modulus in each of the four directions, i.e., 45°, 90°, and 135° clockwise from that direction, is within the range of 2.0 to 3.5 MPa).

2. 2. The polyester film according to claim 1, which has a melting point of 248° C. or higher.

3. 3. The polyester film according to claim 1, having a crystallinity of 25% or more and 40% or less.

4. 4. The polyester film according to claim 1, which has a breaking elongation of 100% or more in both the longitudinal and transverse directions.

5. The polyester film according to any one of claims 1 to 4, which is used for battery exterior packaging.

6. The polyester film according to any one of claims 1 to 4, which is used for pharmaceutical packaging.

Citation Information

Patent Citations

  • Electronic circuit

    JP1986077475A

  • Fuel cell power generating device

    JP1989076679A

  • Packaging material

    JP2000334891A

  • Packing material for battery

    JP2006236938A

  • Polyester film for battery outer packaging and element for battery outer packaging

    JP2011204674A